Strengthening The Halal Value Chain Ecosystem in Era Society 5.0 - Syahidah Rahmah; Wahyuni, Sri; Yusaerah, Nur (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2023)
This research aims to strengthen the capacity of industry players to comply with halal product guarantee regulations in Indonesia. The government's Sehati program, which provides halal socialization and assistance programs, is expected to improve institutional quality and maximize business development in the halal sector. The halal industry is a potential sector that can contribute to the Indonesian economy by providing guarantees and protection for consumers of halal products. This research also seeks to identify the criteria that business actors must meet to comply with halal product guarantee regulations, as well as the supporting and inhibiting factors that they face. The research method is a qualitative literature study using secondary data sources. The data collection method is theory triangulation with descriptive qualitative data analysis. The results of the study indicate that government regulations and halal certification through the Sehati program can increase public confidence that a product is suitable for consumption by Muslim communities worldwide.